ОСНОВНЫЕ НАПРАВЛЕНИЯ В ФИЗИЧЕСКОМ ВОСПИТАНИИ - Умаров, М.Н. (SCIENCE and SOCIETY, 2024)
The study shows that in the physical development and formation of motor abilities, skills and abilities, the experience of sports provides invaluable assistance, in the process of historical development of which the most effective means and methods are selected. At the same time, for a specific contingent of students (age, qualification, gender), appropriate adjustments are required for the dosage of exercises, the mode of their application, etc.